Fibrinogen levels in type II diabetes mellitus patients with microvascular complications - Chikkamath, Vijayalakshmi; Darshan, Arathi; Appajigol, Jayaprakash S.; Angadi, Naveen; T. G., Abhishek (International Journal of Advances in Medicine, 2018)
Background: Diabetes increases the morbidity and mortality due to its propensity to develop micro and macrovascular complications. Recently the role of haemostatic factors, particularly fibrinogen, in atherosclerosis and its complications has invited considerable attention. The present study was conducted to study plasma fibrinogen levels in type II diabetes mellitus patients with microvascular complications. Methods: One hundred patients aged 18years to 60years with type 2 diabetes mellitus with microvascular complications were included in the study. HBA1c, plasma fibrinogen, urine routine examination, fundoscopy, monofilament testing, FBS, PPBS were done. Descriptive statistics was used to analyse data. Results: Out of 100 diabetes patients with microvascular complication studies, 88 patients were found to have hyperfibrinogenaemia. Out of 100 patients 67 patients had HbA1c of more than 8%, and all of them had elevated fibrinogen levels (p <0.0001). The prevalence of hyperfibrinogenemia was higher in patients with diabetic retinopathy (90%), when compared to those without diabetic retinopathy (83.33%) although it was statistically not significant (p=0.266). Conclusions: Hyperfibrinogenemia among type 2 diabetes mellitus patients with microvascular complications was high. Glycaemic control has a significant impact on the fibrinogen levels. Longer the duration of diabetes, there was a higher prevalence of hyperfibrinogenemia.